Ethnic Entrepreneurship and Migration: A Survey from Developing Countries - Marthen L. nDoen; Cees Gorter; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 1998)
This paper explores the phenomenon of ethnic entrepreneurship and migration in developing countries. Our focus is on the decision of migrants to choose a particular site for conducting entrepreneurial activities. A survey of literature is presented in the opening section, in which two approaches, the Structural and Cultural approach, have been used as the basis for this paper. We introduce a profit seeking model in which economic and socio-cultural factors are expected to impact on migrants' decisions to engage in entrepreneurial activities at a particular place. Factors such as degree of competition, market accessibility, capital accessibility, niche concentration, cultural hostility, support network, entrepreneurial experience, migration experience, age, education and period of stay all account for the migrants' decision to choose a particular place.
Keywords: 330; Entrepreneurship-Ansatz; Ethnische Gruppe; Internationale Wanderung; Entwicklungsländer